Transcultural adaptation, content, and internal structure validity evidence of the perceived efficacy and goal setting system – 2 edition for Brazilian children - Nobre, Glauber Carvalho; Gonçalves Duarte, Marcelo; da Silva Ramalho, Maria Helena; Flores Sartori, Rodrigo; Schmitt Marinho, Nádia Fernanda; André Aires Soares, Ívina; Valentini, Nadia Cristina (Frontiers in Psychology, 2023)
The aim was to investigate the validity of evidence of the Perceived Efficacy and Goal Setting System second edition for Brazilian children. Methods: 258 children participated, both sexes (n = 133 girls; 51.6%, 5 to 9 years old (total sample Mage = 7.1, SD = 1.4), from four regions of Brazil. The Perceived Efficacy and Goal Setting System -second edition, was used. Results: experts showed agreement about the high clarity and practical pertinence of the items (content validity coefficient from 98.4% to 100%; Gwet's agreement coefficient from 0.85 to 1.00, p < 0.001). Confirmatory factorial analysis showed adequate adjustment indexes (RMSEA [0.048, 90% C.I. = 0.043 to 0.053], SRMR [0.243], CFI [0.91], RNI [0.91], TLI [0.91], ꭓ 2 /df [1.962]). The multigroup analysis showed configural, metric and scalar invariance of two models for gender (CFI = 0.97; RMSEA, [90%C.I.] = 0.05 [0.03 to 0.07]; metric: Δ RMSEA = 0.001; scalar: Δ RMSEA = -0.004) and age band (5-7 years-old and 8-9 years-old (CFI = 0.94; RMSEA, [90%C.I.] = 0.05 [0.03 to 0.07]; metric: Δ RMSEA = 0.002; scalar: Δ RMSEA = 0.010). The Heterotrait-Monotrait ratio test showed adequate discriminant validity among three dimensions (self-care and productivity[value = 0.76]; self-care and leisure [value = 0.57], productivity and leisure [value = 0.76]). Alpha for polychoric correlations showed an adequate internal consistency for all items and total scale (all α values > 0.70). Composite reliability (Self-care = 0.8; Productivity = 0.81; Leisure = 0.8) reinforce evidence about reliability. The percentage agreement showed adequate item-level testretest reliability (values between 76% and 92%). Conclusion: this scale showed adequate content and internal structure validity evidence to assess the perceived self-efficacy for Brazilian children.